Keutuhan Rumah Tangga Suami di penjara (Studi Kasus di Lembaga Pemasyarakatan Kelas II A Bukittinggi) - Sulfinadia, Hamda; Yanti, Deri; Roszi, Jurna Petri (AL-ISTINBATH : Jurnal Hukum Islam, 2021)
This article discusses the husband as an inmate who is serving a prison term of between 7 and 20 years at the Class II A Penitentiary in Bukittinggi, but on the other hand in married life as husbands, they still have an obligation to provide for their wives and children. The purpose of this study was to determine the views of Islamic law on the fulfillment of the rights and obligations of the husband while he was in prison. This study is a qualitative field research. Based on the research that the author has done, the author concludes that first, husbands who are in prisons can still provide for their wives even though they are modest, and wives can still carry out their obligations to their husbands, although not completely, secondly, wives who still maintain their households are love. , patient and sincere in undergoing the test he is going through and third, in Islamic teachings the husband who is in a correctional institution still has obligations to his children and wife, but if the husband is in a difficult situation and cannot afford it, the husband may provide for his children and wife according to his ability.